ANALISIS PENGARUH DANA PIHAK KETIGA, INFLASI DAN BI RATE TERHADAP RETURN ON ASSETS (ROA) PADA BANK SYARIAH DI INDONESIA PERIODE 2015 - 2019 - Adhista Setyarini (Media Akuntansi, 2021)
This research aims to analyze third-party funds, inflation and BI Rate influence towards Return On Assets (ROA) of sharia banking in Indonesia period of 2015-2019. in Indonesia Approach used in this research is quantitative research approach (using data that can be measured in a scale of numeric/numbers), using secondary data in the form of panel data (pooling of data) that combines data coherently time (time series) data and kerat latitude (cros section) in that period of time. In analyzing the data, researchers using regression test with the help of eviews application 9. The results showed economic the third-party funds effect positive and significant against ROA of sharia banking in indonesia. Inflation has a negative and insignificant relationship towards ROA. BI Rate has a negative and insignificant relationship towards ROA of sharia banking in indonesia.